Faktor internal dan eksternal yang memengaruhi motivasi belajar mahasiswa program profesi dokter - Hamzah, Wafi Ramadhan; Julyani, Sri; Aisyah, Windy Nurul; Amir, Suliati Paduppai; Akib, Marlyanti Nur Rahmah (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Medical students' learning motivation is influenced by internal factors, such as interest, ambition, and self-confidence, as well as external factors, including family support, lecturers, and the learning environment. Students with a strong interest in learning tend to be more motivated to study diligently. Furthermore, personal values, such as ambition and a sense of responsibility towards their profession, can also be powerful motivators. Purpose: To analyze the relationship between internal and external factors influencing medical students' learning motivation. Method: This study used a cross-sectional design with 171 respondents selected using purposive sampling. The study was conducted at Ibnu Sina Hospital, Makassar, over three months, from June to August 2024. Data were collected using a Likert-based questionnaire via Google Forms, and the research instrument was the Motivated Learning Strategies Questionnaire (MSLQ). Results: A total of 72.5% of respondents had high learning motivation, with an average internal factor score of 4.34 and an external factor score of 4.32. A chi-square test showed a significant relationship between internal (p=0.000) and external (p=0.000) factors, with ambition and enjoyment of learning being the most important internal factors, while family support and information technology were the most important external factors. Conclusion: Internal factors (chi-square value of 44.78 and p-value of 0.000) and external factors (chi-square value of 46.75 and p-value of 0.000) have a significant relationship to learning motivation. Students' learning motivation is not formed randomly but is strongly influenced by the quality of their internal and external factors. In this study, internal factors have a more dominant influence on student learning motivation than external factors. Keywords: External Factors; Internal Factors; Learning; Medical Profession; Motivation; Students. Pendahuluan: Motivasi belajar mahasiswa kedokteran dipengaruhi oleh faktor internal, seperti minat, ambisi, dan kepercayaan diri, serta faktor eksternal, meliputi dukungan keluarga, dosen, dan lingkungan belajar. Mahasiswa yang memiliki minat belajar yang tinggi, cenderung lebih termotivasi untuk belajar dengan tekun. Selain itu, nilai-nilai personal, seperti ambisi dan rasa tanggung jawab terhadap profesinya juga dapat menjadi dorongan yang kuat. Tujuan: Untuk menganalisis hubungan faktor internal dan eksternal yang memengaruhi motivasi belajar mahasiswa program profesi dokter. Metode: Desain penelitian menggunakan cross-sectional dengan 171 responden yang dipilih melalui purposive sampling. Penelitian dilakukan di Rumah Sakit Ibnu Sina Makassar dan dilaksanakan selama tiga bulan pada Juni-Agustus 2024. Data dikumpulkan menggunakan kuesioner berbasis Likert melalui google form dan instrumen penelitian menggunakan Motivated Strategies for Learning Questionnaire (MSLQ). Hasil: Sebanyak 72.5% responden memiliki motivasi belajar tinggi dengan rata-rata faktor internal 4.34 dan eksternal 4.32. Uji Chi-Square memperlihatkan hubungan signifikan antara faktor internal (p=0.000) dan eksternal (p=0.000) dengan ambisi dan kesenangan belajar menjadi faktor internal utama, sementara dukungan keluarga dan teknologi informasi menempati faktor eksternal tertinggi. Simpulan: Faktor internal (nilai chi-square sebesar 44.78 dan p-value 0.000) dan eksternal (nilai chi-square sebesar 46.75 dan p-value 0.000) memiliki hubungan yang signifikan terhadap motivasi belajar. Motivasi belajar mahasiswa tidak terbentuk secara acak, melainkan sangat dipengaruhi oleh kualitas faktor internal dan eksternal yang mereka miliki. Pada penelitian ini, faktor internal memberikan pengaruh yang lebih dominan terhadap motivasi belajar mahasiswa dibandingkan faktor eksternal. Kata Kunci: Belajar; Faktor Eksternal; Faktor Internal; Mahasiswa; Motivasi; Profesi Dokter.